Electromagnetic scattering on Janus spheres. (September 2020) - Wauer, Jochen; Rother, Tom
Highlights: Electromagnetic scattering on Janus spheres is described. The corresponding T-matrix is derived by using a least-square scheme. The numerical effort to generate accurate results is much higher as for dielectric spheres. A halo effect leads to a sideward shift of the maximum scattered intensity from the forward direction in special orientations at size parameters less than 6. Abstract: Janus spheres are objects of growing interest in different fields of technology. For example, they can be applied in medicine for a precise drug positioning. They have moreover an enormous potential for the development of new and active materials. Some Janus spheres are already manufactured industrially. Nevertheless, there is a lack of knowledge about the scattering behavior of such objects although it is important not only for diagnostic purposes but also for discovering new applications. In this paper we present the application of the well known T-matrix method to solve the scattering problem of a plane electromagnetic wave on a dielectric sphere whose surface is partially covered with a perfect metal. The application of this approach to a specially oriented Janus sphere reveals an interesting effect for size parameters less than 6.